Statistical Software Output in the Classroom: A Comparison of R and SPSS. (October 2019) - Rode, Jacob B.; Ringel, Megan M.
The current study examines whether R or SPSS output induces greater initial anxiety in students and whether anxiety toward one or both changes after being taught one type of software output throughout the course. The authors each taught an introductory statistics course, with the first course ( n = 43) teaching R output exclusively and the second course ( n = 39) teaching SPSS output exclusively. Students in both courses were given surveys assessing their anxiety and confidence toward R and SPSS output on the first and last days of class. Students initially reported greater anxiety and lower confidence when viewing R compared to SPSS output. However, the initial difference between R- and SPSS-related anxiety and confidence level disappeared when students were taught R and decreased substantially when students were taught SPSS. The results suggest that although R output may seem more intimidating initially, students adapt to it as well as they do to SPSS.